2013
DOI: 10.1586/14737167.2014.864559
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of the Iranian version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire for patients with Bone Metastases: the EORTC QLQ-BM22

Abstract: The aim of the present study was to evaluate the psychometric properties of the measure among a sample of Iranian patients with bone metastases. One hundred and seventy-seven patients with bone metastases undergoing various treatments were recruited from Imam Khomeini Hospital in Tehran to participate in the study. The coefficient alpha affirmed internal consistency reliability of the Quality of Life Questionnaire for patients with Bone Metastases (QLQ-BM22). This measure discriminated well between subgroups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The discriminant validity in both questionnaires was also satisfactory. That generally con rms the results obtained for the international study and follows data for Iranian and Spanish version for QLQ-INFO25 [24,33,34]. The high correlation between some items with scales other than their own (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The discriminant validity in both questionnaires was also satisfactory. That generally con rms the results obtained for the international study and follows data for Iranian and Spanish version for QLQ-INFO25 [24,33,34]. The high correlation between some items with scales other than their own (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…That means the tools can be used to compare various groups. The test-retest reliability for both modules was good as it was in other studies [24,33,34].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Three instruments were assessed for floor and ceiling effects in four studies 30 , 34 , 38 , 39 . All studies had an acceptable result, with no floor and ceiling effects observed.…”
Section: Resultsmentioning
confidence: 99%
“…This study sought to evaluate a tool that met this need and addressed issues related solely to the characteristic symptoms of patients with bone metastasis in a simple and objective way. The QLQ-BM22 is an instrument available in the literature that has been translated and validated for use in Japan, Iran and Poland (4,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%